Dental tourism: Examining tourist profiles, motivation and satisfaction. (August 2017) - Jaapar, Mustaffa; Musa, Ghazali; Moghavvemi, Sedigheh; Saub, Roslan
Abstract: Despite the overwhelming interest in medical tourism research, knowledge in dental tourism, which is its subspecialty, remains limited. This study is the first to measure tourist profiles, travel motivation and satisfaction among inbound dental tourists in Malaysia. We purposely sampled twelve selected private dental clinics in Kuala Lumpur, Selangor, Melaka and Penang; and distributed the questionnaires to their inbound dental tourists. A total of 196 inbound tourists responded to the questionnaire, mainly from Southeast Asia, Australia, New Zealand and Europe. In order of importance, the main motivation factors were dental care quality, dental care information access, and cost-savings. Tourists were extremely satisfied with dental care services received in the country. While dental care quality, dental care information access and supporting services positively influenced tourist satisfaction; cost-savings and cultural similarities had negative influences. Based on the research findings, we propose some managerial and marketing recommendations. Highlights: We purposely sampled 196 inbound dental tourists in Malaysia. Important motivations are dental care quality, information access, and cost-savings. Information access and dental care quality positively influenced satisfaction. Cost-savings and cultural similarity negatively influenced satisfaction. We propose some marketing and managerial recommendations.